(untitled) (Research, Society and Development, 2023)
Pregnancy is a period in which women are prone to physiological, metabolic, and hematological changes, resulting in the practice of self-medication during this period. This is a concerning issue due to the potential risks it can pose to health, influenced in Brazil by outdated prescriptions, media, and recommendations from third parties. In the case of pregnant women, the concern is greater, as this practice can cause irreversible damage to the developing fetus, such as teratogenicity and drug withdrawal. The objective of this study was to discuss the danger of irrational use of medication during pregnancy and its potential risks to the health of the fetus and mother. This work is an integrative literature review, where the selection of studies was carried out in online databases: Scielo, Pubmed, and Capes, between the years 2017 to 2022. Following the inclusion and exclusion criteria, 11 articles were selected. It is worth concluding that it is the role of the pharmacist to promote educational campaigns, regularly update knowledge about medications and strategies to combat self-medication, establish greater control in dispensing, especially when it comes to pregnant women, recognizing the dangers and possible drug interactions, seeking, in short, to reduce cases of self-medication, morbidity and mortality, malformations, and occurrences during and after the gestational period, establishing progress in the quality of life for the mother and fetus, where it is recognized that the most sought-after medications by pregnant women are analgesics, antacids, vitamins, antiemetics, anti-inflammatories, and antibiotics.